Lung function and nonalcoholic fatty liver disease: a Mendelian randomization study - Jiran Shen; Yue Wang; Sijing Zhou; Min Tang; Min Li; Rui Han; Ran Wang (Archives of Medical Science)
Introduction Associations of pulmonary function as evaluated by forced expiratory volume in 1 s (FEV1) and forced vital capacity (FVC) with non-alcoholic fatty liver disease (NAFLD) have been reported in observational studies. Nevertheless, observational studies are susceptible to bias and reverse causality, making it difficult to infer the existence and direction of causality. We aimed to evaluate the causal effect of pulmonary function on NAFLD using the Mendelian randomization (MR) method.